2003
DOI: 10.1136/gut.52.6.791
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and location of cardiac mucosa: an autopsy study in embryos, fetuses, and infants

Abstract: Background: The incidence of gastric cardiac adenocarcinoma has increased in the last decades. Gaining insight into the pathogenesis of this lesion is hampered by the limited knowledge of the origin and histology of cardiac mucosa (CM). Currently, the location, extent, and even the existence of CM are controversial. Aims: We studied the development of the gastro-oesophageal junction (GOJ) in embryos, fetuses, and infants to clarify if CM is a normal structure at birth and where it is located. Subjects: Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 14 publications
5
44
1
1
Order By: Relevance
“…Immunohistochemistry for CK5,7,8,13,18,19, and 20 was performed. Antibody staining was then graded for location, intensity, and degree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry for CK5,7,8,13,18,19, and 20 was performed. Antibody staining was then graded for location, intensity, and degree.…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier done a histological study on mucosal development in the EGJ of embryos and fetuses [19] . In this study, CM was defined as a structure composed of columnar foveolar and surface epithelium overlying glandular structures containing no parietal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Because the incidence and extent of the cardiac glands were linked to excessive gastroesophageal reflux, this led Chandrosoma et al [9] to speculate that cardiac glands may be an acquired change from esophageal squamous mucosa. However, cardiac glands were subsequently identified in most children, the newborn, and even in fetuses [10][11][12], suggesting that they are present from early in life, representing a functionally distinct, albeit small, anatomical region of the normal stomach.…”
Section: The Gastric Cardia and Gca: Anatomy And Definitional Issuesmentioning
confidence: 99%
“…Digestive Endoscopy © 2017 Japan Gastroenterological Endoscopy Society and infant cases, De Hertogh and colleagues reported that cardiac mucosa exists since 13 weeks gestational age in all samples and is present around the esophageal perimeter, has a mean length of 0.3-0.6 mm, and is located proximal to or at the EGJ if it is defined as the angle of His. 30 To avoid over-or underdiagnosis of endoscopically suspected BE, firm diagnosis criteria were established. Thus, the Montreal Global Consensus Document revised the definition of BE to involve not only intestinal-type metaplasia but also pure gastric cardia-type metaplasia as part of the spectrum of BE.…”
Section: Is Be a Congenital Or An Acquired Disease?mentioning
confidence: 99%